Strava as a discursive field of practice: Technological affordances and mediated cycling motivations. (April 2020) - Rivers, Damian J.
Highlights: A content approach is adopted with data from 162 registered cyclists on Strava. The discursive practices within the Online Social Fitness Network are explored. Discourse relating to self-tracking, data, community and dependency are identified. Abstract: The number of interactive fitness technologies, applications and networks which have gamified and biomedicalized real-world activities such as cycling have increased significantly over recent years (e.g., Endomondo, Fitocracy, Runtastic, Map My Ride, Nike+ Running and Zwift). Given the rising popularity of these Online Social Fitness Networks (OSFNs), it is important to understand their motivational affordances and the discursive communities of practice which they facilitate. Framing Strava as a case in point, the current article adopts a content analysis approach to data drawn from 162 registered cyclists on Strava to explore the motivational affordances and discursive practices dominant within the Strava OSFN. The perceived motivational affordances of the technology are shown to reflect a coherent Strava discourse relating to self-tracking, data, community and dependency.